Evaluation of the depth of submandibular gland fossa and its correlation with mandibular canal in vertical and horizontal locations using CBCT - P Ramaswamy; Ch Saikiran; B Mrudula Raju; Myla Swathi; Davuluri Divya Teja (Wolters Kluwer Medknow Publications, 2020)
Introduction: Dental implant is the most preferable option for the replacement of missing teeth because of its advantage of maintaining the structural and functional integrity of bone, like that of a natural tooth. Aim and Objectives of the Study: Aim of this study is to evaluate the depth of submandibular gland fossa and its relationship with the mandibular canal, based on gender and side of the mandible. Materials and Methods: 100 CBCT scans of both males and females were acquired. The deepest region of submandibular gland fossa and the superior, parallel, and the inferior relationship of the mandibular canal to submandibular gland fossae were obtained. Results: The mean ± SD of the depth of the submandibular gland fossa on the right side in males and females were 1.69 ± 0.73 mm and 1.62 ± 0.58mm, respectively, and those on the left were 1.69 ± 0.61 mm and 1.56 ± 0.42 mm, respectively. The deepest region in both the genders was above the infra-alveolar canal. Conclusion: Males showed greater depths when compared to females, Right side of the mandible showed greater depth when compared to the left side in both genders. Therefore, careful evaluation of alveolar bone thickness during implant placements is of great importance in males.